2004
DOI: 10.1364/ol.29.002479
|View full text |Cite
|
Sign up to set email alerts
|

High-contrast microscopy of semiconductor and metal sites in integrated circuits by detection of optical feedback

Abstract: High-contrast microscopy of semiconductor and metal sites in integrated circuits is demonstrated with laser-scanning confocal reflectance microscopy, one-photon (1P) optical-beam-induced current (OBIC) imaging, and detection of optical feedback by means of a commercially available semiconductor laser that also acts as an excitation source. The confocal microscope has a compact in-line arrangement with no external photodetector. Confocal and 1P OBIC images are obtained simultaneously from the same focused beam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…1b). Previous research utilised simple post-processing of this image pair to discriminate metallic and semiconductor sites in 3D and localise defects within the differentiated regions [1,2].…”
Section: Optical Feedback Thermography (Oft)mentioning
confidence: 99%
“…1b). Previous research utilised simple post-processing of this image pair to discriminate metallic and semiconductor sites in 3D and localise defects within the differentiated regions [1,2].…”
Section: Optical Feedback Thermography (Oft)mentioning
confidence: 99%
“…[2][3][4][5] The SMI-based imaging can be classified into two classes. In one class, the LD is set to operate at a steady state, [6][7][8][9] using SMI in a confocal microscope configuration. The laser is operated at a constant bias current.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, LFI has been extensively employed in general remote sensing applications such as metrology, profilometry, and vibrometry [7,8,10]. Using LFI technique in optical laser scanning microscopy has been successfully demonstrated [2,[11][12][13][14][15]. In some of the early studies, it was suggested that despite the non-linearities in the sensing process, which can be related to the dynamics of semiconductor lasers under the feedback regime, CLFM possesses all the functionality of CLSM [2].…”
mentioning
confidence: 99%
“…Surface microscopy of biological cells has also been demonstrated [14,15]. Furthermore, the possibility of depth sectioning has been investigated to some extent by imaging the surface at different axial depths [2,13]. Although CLFM has been used for surface microscopy of objects and for micro-profilometry [2,[11][12][13]15], its in-depth (from deep within a scattering sample) microscopic imaging potential for visualisation of micro-structures has not been fully explored to date.…”
mentioning
confidence: 99%
See 1 more Smart Citation